Current Updates of Connection Between Food Allergies and Atopic Dermatitis : a Literature Review - Muhammad Farrell Rikhad; Rendy Wijaya (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2026)
Introduction: The relationship between food allergy (FA) and atopic dermatitis (AD) involves a complex, bidirectional interplay often associated with the